Effectiveness of an integrated care intervention on supervisor support and work functioning of workers with rheumatoid arthritis. Issue 4 (13th February 2017) - van Vilsteren, Myrthe; Boot, Cécile R. L.; Twisk, Jos W. R.; van Schaardenburg, Dirkjan; Steenbeek, Romy; Voskuyl, Alexandre E.; Anema, Johannes R.
Abstract: Purpose: In this manuscript, we evaluated the effectiveness of an intervention programme consisting of integrated care and a participatory workplace intervention on supervisor support, work instability and at-work productivity after 6 months of follow-up among workers with rheumatoid arthritis (RA). Methods: We conducted a randomized controlled trial; we compared the intervention programme to usual care. Eligible patients were diagnosed with RA, had a paid job (> 8 h per week) and who experienced, at least, minor difficulties in work functioning. Supervisor support was measured with a subscale of the Job Content Questionnaire, work instability with the Work Instability Scale for RA, and at-work productivity with the Work Limitations Questionnaire. Data were analyzed using linear regression analyses. Results: A beneficial effect of the intervention programme was found on supervisor support among 150 patients. Analyses revealed no effects on work instability and at-work productivity. Conclusion: We found a small positive effect of the intervention on supervisor support, but did not find any effects on work instability and at-work productivity loss. Future research should establish whether this significant but small increase in supervisor support leads to improved work functioning in the long run. This study shows clinicians that patients with RA are in need of efforts to support them in their work functioning. Implications for Rehabilitation: Rheumatoid arthritis (RA) is a chronic inflammatory disease with a severe impact on work functioning, even when a patient is still working. It is important to involve the workplace when an intervention is put in place to support RA patients in their work participation. Supervisor support influences health outcomes of workers, and it is possible to improve supervisor support by an intervention which involves the workplace and supervisor.